2019
DOI: 10.21203/rs.2.368/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Vessel Density of the Patients with Narrow Antenior Chamber after an Acute Intraocular Pressure Elevation Observed by OCT Angiography

Abstract: Background:Although the pathogenesis of glaucoma is not fully understood ,an elevated intraocular pressure (IOP) is a major factor contributing to its development and progression. The aim of this study was to investigate the changes in the vessel densities of the macula and optic nerve head (ONH) after an acute elevation in the intraocular pressure (IOP) observed using optical coherence tomography angiography (OCTA). Methods: This was a prospective comparative study of subjects with narrow anterior chamber ang… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Some investigations have indicated that anterior segment ischaemia caused APAC and that retinal ischaemia may be present after an APAC episode 29 . In addition, Ma et al found that macular and papillary VD decreased significantly in eyes with narrow anterior chambers after an acute IOP elevation recently 30 . Therefore, the dropout of macular VD in APAC eyes may be due to the elevated IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have indicated that anterior segment ischaemia caused APAC and that retinal ischaemia may be present after an APAC episode 29 . In addition, Ma et al found that macular and papillary VD decreased significantly in eyes with narrow anterior chambers after an acute IOP elevation recently 30 . Therefore, the dropout of macular VD in APAC eyes may be due to the elevated IOP.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have agreed that intraocular pressures up to 20 mmHg showed no impact on macular VD. 28,29 This may help to explain the intraocular and mean arterial pressure findings in the regression models. For example, an increase in mean arterial pressure correlated with a decrease in VD only in the macular region.…”
Section: Vessel Density (%)mentioning
confidence: 97%
“…Snižováním NOT u mladých jedinců s vysokým NOT zaznamenal Holló zvýšení VD [23]. Obráceně, po jeho zvýšení nad 20 mmHg hustota cév v makule a peripapilárně významně poklesla [24].…”
Section: Diskuzeunclassified